2016
DOI: 10.1038/srep38434
|View full text |Cite
|
Sign up to set email alerts
|

Individuation of objects and object parts rely on the same neuronal mechanism

Abstract: Recent results have shown that participants can enumerate multiple parts of a single object as efficiently as multiple distinct objects, suggesting a shared mechanism for individuation of objects and object parts. Here we used the subitizing phenomenon to investigate the neural mechanism underlying the individuation of object parts. In two experiments, we measured a lateralized EEG response (N2pc) previously associated with individuation of multiple objects. In line with the subitizing effect, participants’ er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
(112 reference statements)
1
12
0
Order By: Relevance
“…If parts of an object have to be enumerated, in the special case where no other objects are present, parts can be subitized as efficiently as distinct objects (Poncet et al, 2016;Porter et al, 2016;Wurm et al, 2019; see also Experiment 1). This is because the single object with parts is initially individuated at no cost by attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If parts of an object have to be enumerated, in the special case where no other objects are present, parts can be subitized as efficiently as distinct objects (Poncet et al, 2016;Porter et al, 2016;Wurm et al, 2019; see also Experiment 1). This is because the single object with parts is initially individuated at no cost by attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies have reported that subitizing parts of an object is as efficient as subitizing independent objects (Porter et al, 2016) and evoke the same neuronal signature (Poncet et al, 2016;Wurm et al, 2019). These results were taken to argue that components of an object occupying distinct locations, such as parts, can be individuated in parallel and that individuation is not bound to (distinct) objecthood.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen young (mean age 23.3, range 19-27, 14 female) and 20 older volunteers (mean age 68.1, range 63-77 years, 10 female) were tested in Experiment 2. The sample size was determined based on previous studies (Poncet et al, 2016;Porter et al, 2016;Trick et al, 1996;Watson et al, 2005b). No participant reported a history of neurological or psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Porter et al (2016) found that multiple parts bound to a single object can be enumerated as efficiently as multiple distinct objects. In addition, a neural signature of target individuation varies as a function of object-part numerosity in the same way as in the case of distinct objects, suggesting that the same neural mechanism triggers individuation of multiple objects and multiple parts of a single object (Poncet et al, 2016, Wurm et al, 2019. Does aging affect the sufficient requirement for individuation in enumeration?…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the visual number sense relates to properties as object area and density, neural responses of numerosity-selective cognitive systems were found to be invariant to all visual features except quantity [28,12]. Furthermore, studies on cognitive neuroscience have shown that the perception of number functions independently from mathematical reasoning [12,33]. All these findings suggest that visual number sense is a perceptual property that emerges directly from the visual sensory input.…”
Section: Related Workmentioning
confidence: 99%